PENGARUH BAURAN PEMASARAN TERHADAP KEPUASAN PELANGGAN PADA TOKO MYARUMI KABUPATEN SIDENRENG RAPPANG - Widia Andayani Andayani; Suriadi Suriadi; Fadlina Fadlina (Universitas Ichsan Sidenreng Rappang, 2024)
Customer satisfaction is the most urgent thing in the business field because it is a determining factor in the success of a company, prices that are not affordable will make customers feel less satisfied. The purpose of this study was to determine whether the marketing mix of Product (X1), Price (X2), Place (X3) and Promotion (X4) has an effect on Customer Satisfaction at Toko Myarumi Sidenreng Rappang Regency, both partially and simultaneously.The method used in this research is quantitative research method with a type of correlation research. The data used in this study are primary data obtained from distributing questionnaires to customers of Toko Myarumi Sidenreng Rappang Regency, the population in this study is unlimited so that the researchers conducted a sample of 96 respondents using the lemeshow formula, then the data obtained were processed using the help of the SPSS program. The data analysis method used in this research is multiple linear regression analysis.The results showed that the marketing mix of Product (X1), Price (X2), Place (X3) and Promotion (X4), both partially and simultaneously had a positive and significant effect on Customer Satisfaction at Toko Myarumi Sidenreng Rappang Regency. Keywords: Marketing Mix and Customer Satisfaction.